Hyperbaric oxygen therapy in the surgical approach to an irradiated patient - Antônio Figueiredo Caubi; Ricardo José de Holanda Vasconcelos; Belmiro Cavalcanti do Egito Vasconcelos; Hécio Henrique Araújo de Morais; Ricardo Wathson Feitosa de Carvalho (Faculdade São Leopoldo Mandic, 2008)
Cancer is the terminology applied to a set of more than one hundred diseases that have disorderly cell growth in common. The treatmentof cancer can be performed by surgery, radiotherapy, chemotherapy, or bone marrow transplant. In the region of the head and neck,radiotherapy results in a series of complications in the patient, such as hypovascularization of the irradiated tissues, with reduced demand of oxygen and cells, and there is risk of the occurrence of osteoradionecrosis after tooth extraction, leading to the need for a differentiated approach to these patients. Of the therapeutic conduct adopted in the approach to irradiated patients, hyperbaric oxygen therapy is a well established resource, as the therapeutic principle of this modality enables the restoration of an adequate process of tissue repair. In this study, a clinical case is related, of the use of hyperbaric oxygen therapy as an adjuvant procedure, before and after multiple tooth extractions, in a patient irradiated in the head and neck region, obtaining success with cicatricial repair without complications.